Effects of socioeconomic status on physical and mental health of hemodialysis patients in Japan: differences by age, period, and cohort - Sugisawa, Hidehiro (Int J Nephrol Renovasc Dis, 2016)
STUDY PURPOSE: Whether or not socioeconomic status (SES)-related differences in the health of hemodialysis patients differ by age, period, and birth cohort remains unclear. We examined whether SES-related gaps in physical and mental health change with age, period, and birth cohort for hemodialysis patients. METHODS: Data were obtained from repeated cross-sectional surveys conducted in 1996, 2001, 2006, and 2011, with members of a national patients’ association as participants. We used raking adjustment to create a database which had similar characteristics to the total sample of dialysis patients in Japan. SES was assessed using family size-adjusted income levels. We divided patients into three groups based on their income levels: below the first quartile, over the second quartile and under the third quartile, and over the fourth quartile. We used the number of dialysis complications as a physical health indicator and depressive symptoms as a mental health indicator. We used a cross-classified random-effects model that estimated fixed effects of age categories and period as level-1 factors, and random effects of birth cohort as level-2 factors. RESULTS: Relative risk of dialysis complications in respondents below the first quartile compared with ones over the fourth quartile was reduced in age categories >60 years. Mean differences in depressive symptoms between respondents below the first quartile and ones over the fourth quartile peaked in the 50- to 59-year-old age group, and were reduced in age groups >60 years. In addition, mean differences varied across periods, widening from 1996 to 2006. There were no significant birth cohort effects on income differences for dialysis complications or depressive symptoms. CONCLUSION: The number of dialysis complications and depressive symptoms in dialysis patients were affected by income differences, and the degree of these differences changed with age category and period.